Impact of Ethical Training on Auditors’ Ethical Decision Making in Morocco - Arrami , Nawfel; QingXiang, Yang (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2022)
The purpose of this study is to investigate the moderating role that can play ethical training in increasing auditors’ level of ethics. Therefore, this research will test any significant differences between the two groups through a multi-group moderation analysis. The first group represents auditors who took an ethics course before, and the other group represents auditors who did not previously take any course. This comparison will be performed based on the relationships between the variables in our model, namely ethical judgment, ethical intention, moral identity centrality, and perceived moral intensity. The sample of this study is mainly external senior auditors operating in audit firms in Morocco. We could obtain 125 usable responses, and we processed data with SmartPLS software. The results show that auditors’ moral identity impacts their ethical judgment positively and significantly, and the effect is more substantial for the group of auditors who took an ethics course before. Moreover, taking an ethics course seems to moderate also the positive and significant relationship between auditors’ ethical judgment and their ethical intention. However, the results were opposite to what we expected concerning the relationship between perceived moral intensity and auditors’ ethical judgment. Thus, ethical training seemed to moderate the positive relationship negatively.